PERANAN PENYULUHAN PERTANIAN TERHADAP PRODUKTIVITAS KERJA PETANI SAYURAN DI KECAMATAN KUMPEH ULU KABUPATEN MUARO JAMBI - Herdiyansyah, Rikky (Universitas Jambi, 2018)
This study aims to determine the work productivity of vegetable farmers and determine the relationship between agricultural extension and the work productivity of vegetable farmers in Kumpeh Ulu District, Muaro Jambi Regency. High or low productivity of vegetable farmers work is influenced by the amount of production produced by farmers and the amount of revenue received by farmers. There is a real relationship between agricultural extension with the work productivity of vegetable farmers, this shows that the more often farmers get agricultural extension activities, farmers will be more motivated to increase productivity